Production of Liquid Organic Fertilizer Made From Kirinyuh Leaves with Added Chicken Bone Meal Using the EM4 Bioactivator - Nabila Yogi Valentina Sari; Mutiara Zulvita Ramadhani; Ely Kurniati (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Continuous use of chemical fertilizers leads to decreased soil fertility, nutrient imbalance, and environmental pollution. One alternative fertilizer is liquid organic fertilizer (POC), which can improve the physical, chemical, and biological properties of the soil while providing nutrients. Kirinyuh leaves (Chromolaena odorata) have great potential as a raw material for POC due to their high macro and micro nutrient content and bioactive compounds that support plant growth. This study aims to produce liquid organic fertilizer from kirinyuh leaves with the addition of chicken bone meal that meets the standards of the Regulation of the Minister of Agriculture of the Republic of Indonesia Number 261/KPTS/SR.310/M/4/2019, and to evaluate the effect of fermentation time and dosage of chicken bone meal on fertilizer quality. Fertilizer is made through a fermentation process using EM4 as a bioactivator with variations in fermentation time and dosage of chicken bone meal. The results showed that fermentation time and dosage of chicken bone meal significantly affected the quality of POC. The concentrations of N, P, and K increased until the 21st day of fermentation due to increased microbial activity in decomposing organic matter, then decreased slightly or did not increase significantly on the 28th day as it entered the fermentation maturation phase. The addition of chicken bone meal increased the concentration of nutrients, especially phosphorus and potassium, while the C/N ratio increased until the 21st day and decreased on the 28th day, indicating that the decomposition process was effective.